Inborn errors of metabolism in palliative care. Issue 10 (3rd September 2021) - Harputluoğlu, Nilgün; Köse, Melis; Yılmaz, Ünsal; Çelik, Tanju
Abstract: Background: In parallel with the increase in the number of children with life‐limiting or life‐threatening diseases, the need for and right to pediatric palliative care is also increasing. This study aimed to examine the metabolic diseases, evaluate the symptoms, and review the needs of children who were admitted to the pediatric palliative care service. Methods: Following the approval of the local ethics committee (18/7/2019‐107), the computer records of patients hospitalized in the pediatric palliative care service between December 1, 2018 and January 6, 2019 were reviewed retrospectively. Dr Behçet Uz Children's Hospital, Pediatric Palliative Care Center is third center in Turkey. Our pediatric palliative care center has one year of experience. Results: In the study period, there were 101 patients who were hospitalized in the pediatric palliative care service. Eighteen patients (19.7%) diagnosed with inborn errors of metabolism were included in the study. The mean age was 3.2 ± 2.1 (0–8) years. Although it could not be shown statistically, the duration of hospitalization of patients with congenital malformation was long. Conclusion: Pediatric palliative care provides the best care with the control of various symptoms in neurodegenerative congenital metabolic diseases that do not have treatment or treatment, but progressive symptoms cannot be prevented.